Use of Molecular Hydrogen in Food Technologies - Alwazeer, Duried; Engin, Tunahan (Turkish Journal of Agriculture - Food Science and Technology, 2022)
Molecular hydrogen is a colorless, odorless, tasteless, non-toxic, flammable, and diatomic gas. Molecular hydrogen is dissolved directly in water to be used in the form of hydrogen-rich water (HRW) to keep the freshness of fruits and vegetables. The shelf-life of the product was increased and the quality attributes were maintained when hydrogen was applied to some food products such as milk, tea, and fruit juices. Some grain products and greens grew rapidly and their antioxidant substance levels increased when they were supplied with hydrogen-rich water. Molecular hydrogen has shown an important application in food drying in recent years, was used especially in reducing atmosphere drying (RAD) technology. Few studies have been conducted on the use of molecular hydrogen in food products. Due to its various positive effects, the use of molecular hydrogen in the food industries using different techniques and processes could be encouraged by the presence review